THE USE OF YOUTUBE ANIMATION VIDEOS IN IMPROVING ENGLISH VOCABULARY IN PRESCHOOL CHILDREN AT SPS SEULANGA CERIA - Siti Ayyuwa Indana; Rizka Marlisa Aini; Zahria Amalina (Journal of Innovative and Creativity (Joecy), 2026)
Purpose. Vocabulary mastery is one of the fundamental aspects of English language learning, particularly for preschool children who are in the critical stage of language acquisition. However, many young learners experience difficulties in understanding, memorizing, and pronouncing English vocabulary because of limited exposure to English and the use of less engaging instructional media. Therefore, this study aimed to investigate the effectiveness of YouTube animation videos in improving English vocabulary mastery among preschool children at SPS Seulanga Ceria, Banda Aceh. Materials and Methods. This study employed a quantitative approach using a pre-experimental method with a One-Group Pre-test and Post-test Design. The participants consisted of 15 preschool children aged 5–6 years selected from SPS Seulanga Ceria. Data were collected through vocabulary tests administered before and after the implementation of YouTube animation videos as the instructional medium. The collected data were analyzed using descriptive statistics, the Shapiro–Wilk normality test, and the Paired Sample t-test with the assistance of SPSS software. Results. The findings revealed a substantial improvement in the children's English vocabulary achievement after the intervention. The mean pre-test score was 45.33, whereas the mean post-test score increased to 82.33, resulting in a mean gain of 37.00 points. The Shapiro–Wilk test indicated that both pre-test and post-test data were normally distributed (pre-test p = 0.051; post-test p = 0.415). Furthermore, the Paired Sample t-test produced a significance value of 0.000 (p < 0.05), demonstrating a statistically significant difference between the pre-test and post-test scores. Conclusions. The findings indicate that YouTube animation videos are an effective audiovisual learning medium for enhancing English vocabulary mastery among preschool children. The integration of visual illustrations, audio pronunciation, and repetitive exposure creates an engaging learning environment that facilitates vocabulary acquisition. Therefore, YouTube animation videos can be considered an effective instructional medium for early childhood English learning..